Importance of Quantum Physics to Arouse Interest in Science (Research, Society and Development, 2021)
For students, the first contacts with science were probably established in childhood through the media, in the form of images or fictional texts. Only near high school does systematic knowledge appear, with laws, rules, conventions, etc. In general, physical phenomena are presented as governed by mathematical formulas, without an overall view, without the history of science and its characters, without the characteristic harmony of nature. Does this way of teaching and evaluating through formulas awaken in the student an interest in science? Science has, among others, the objective of generating knowledge to understand, understand and take advantage of the phenomena of our physical world for the benefit of man's well-being. The theme of this article focuses on the importance of Quantum Physics in High School and also to awaken interest in science in the short-term student of Computer Science. As a methodology, a qualitative research was developed in the sense of an action research as a work strategy, conceived with the purpose of understanding and analyzing the previous knowledge in Quantum Physics of students in the first semesters of the Computer Science course at Ceunsp University, proposing as an intervention, the realization of a Quantum Physics workshop, with reflection on its ability to awaken in students the interest in science.